Combined effects of Climate Smart Agriculture and Climate Information Services on rice farmers’ yield, income and food consumption score in Mali - Diallo, Aboubacar; Samake, Mahamoudou; Kansaye, Aly; Diarra, Bah Afoussatou; Guindo, Samuel; Akpoffo, Marius; Dossou-Yovo, Elliott Ronald (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This study aimed to identify predictors of combined use of climate information services (CIS) and climate-smart technologies (CSAs) and assess their impacts on rice producers' yield, gross income, and food security. Primary data from 240 rice farmers across four environments were collected using the Randomized Controlled Trial (RCT) approach of which 60 farmers have access to both CSA and CIS, 60 farmers have access to CSA only, 60 farmers have access to CIS only and 60 farmers have neither access to CSA nor to CIS. Logit regression analyzed determinants of CSA and CIS adoption. Results indicated that seasonal forecasts, daily forecasts, and rainy season start date forecasts were the main types of climate information received by farmers. Flood-tolerant and drought-tolerant rice varieties, composting, and integrated rice-legume systems were key CSA technologies adopted by farmers. Factors like producer gender, age, training access, fragmented field and access to telephone were the main factors affecting combined access to CSA and CIS. Rice yield, income, and food consumption scores were increased by 1,017 kg/ha, 97,240 FCFA/ha and 2.15, respectively when the farmers have combined access to CSA and CIS compared to farmers who have neither access to CSA nor access to CIS. This suggests potential benefits for enhancing resilience to climate change and improving productivity and food security in agricultural households.